PBT-Alumina Composite Particles, Methods, and Molded Articles
Patent Information
- Application Number
- JP2024545901
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-02
- Filing Date
- 2023-02-02
- Publication Date
- 2025-02-28
Smart Images

Figure 2025505570000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority from European Patent Application No. 22154749.0, filed February 2, 2022. European Patent Application No. 22154749.0 is incorporated herein by reference in its entirety.
[0002] FIELD OF THEINVENTION The present disclosure relates generally to ceramic-thermoplastic composites, and more particularly, but not exclusively, to PBT-alumina composite particle powders and related processes and articles. [Background technology]
[0003] background Currently, there are only a very limited number of ceramic-polymer composites with a large ceramic percentage. Known ceramic-polymer composites typically contain significantly less than 50 volume percent ceramic and significantly more than 50 volume percent polymer.
[0004] The first category of such ceramic-polymer composites relies on a thermosetting approach, where a monomer is combined with a porous ceramic structure and cured to form a composite, but this approach generally requires undesirably long curing times, and the final product generally depends on the size of the pores in the ceramic and the viscosity of the resin.
[0005] A second category of such ceramic-polymer composites relies on thermoplastic polymers. Generally, thermoplastic polymers do not require time to harden, instead, they can be melted simply by heating and then cooled to solidify the thermoplastic polymer, thereby allowing for relatively fast processing. Thermoplastics and ceramic fillers are blended to achieve certain properties, including stiffness and strength. However, typically, the ceramic filler content in such thermoplastic polymers is limited to much less than 50% by volume due to the constraints of conventional compounding techniques. For example, in this type of conventional approach, the ceramic filler is added to the polymer and the mixture is compounded and palletized in an extruder. Generally, the dispersion and distribution of the ceramic filler in the polymer matrix is highly dependent on the type of ceramic and polymer, other additives and coupling agents, mixing speed, shear rate, temperature, and various other parameters. Due to at least these constraints, having a large percentage of ceramic filler (e.g., greater than 50% by volume) in a polymer matrix can be challenging, for example, it can damage the extruder screw (depending on the hardness of the ceramic) and can degrade the polymer due to shear and heat.
[0006] A third category of such ceramic-polymer composites relies on a more recently identified approach known as "cold sintering". Various aspects of this may be described in U.S. Patent Application Publication No. US2017 / 0088471 and PCT Application Publication Nos. (1) WO2018 / 039620, (2) WO2018 / 039628, (3) WO2018 / 039619, and (4) WO2018 / 039634. However, one drawback to cold sintering is that not all ceramics can be effectively cold sintered. For example, generally, certain structural ceramics such as aluminum oxide, zirconia, titanium oxide, and silicon carbide cannot be cold sintered. Furthermore, structures produced by cold sintering typically utilize a ceramic as the matrix and a polymer as the filler, which generally results in different structural properties and different suitability for various end-use applications.
[0007] A fourth category of such ceramic-polymer composites may involve dissolving an amorphous polymer in a solvent and adding ceramic particles to the polymer-solvent mixture. For example, a spouted-bed granulation process can be used to create polymer-coated ceramic powders, as described in Wolff, Composites Science and Technology 90 (2014) 154-159. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] U.S. Patent Application Publication No. US2017 / 0088471 [Patent Document 2] PCT Application Publication No. WO2018 / 039620 [Patent Document 3] PCT Application Publication No. WO2018 / 039628 [Patent Document 4] PCT Application Publication No. WO2018 / 039619 [Patent Document 5] PCT Application Publication No. WO2018 / 039634 [Non-patent literature]
[0009] [Non-Patent Document 1] Wolff, Composites Science and Technology 90 (2014) 154-159 Summary of the Invention
[0010] overview The present disclosure includes PBT-alumina composite powders having a large percentage of alumina (i.e., 50% by volume or more) in which individual PBT particles are bonded to alumina particles and / or other PBT particles, as well as methods of producing such composite powders and methods of forming composite parts from such composite powders. However, unlike previous polymer-ceramic composite powders in which individual polymer particles were completely dissolved and / or fused in an attempt to form a substantially continuous shell around a ceramic core, the present composite powders differ in that the individual PBT particles within the composite particles largely retain their individual properties and do not form a smooth or continuous shell around the individual ceramic particles. The present composite powders also exhibit a high degree of uniformity in the overall distribution of PBT and alumina particles within the agglomerated composite powder. Thus, and unexpectedly, even in the absence of a substantially continuous PBT shell surrounding the alumina particles, parts molded (e.g., via compression or injection molding) from the present composite powders typically exhibit excellent mechanical properties (e.g., flexural modulus, flexural strength, flexural strain, relative density), and such mechanical properties are substantially consistent across multiple parts molded from one of the present composite powders.
[0011] The PBT-alumina composite powder comprises a plurality of composite particles, each of which comprises one or more aluminum oxide (Al2O3) particles and a plurality of polybutylene terephthalate (PBT) particles, where for each of the composite particles, at least some of the PBT particles are physically bonded to Al2O3 particles, and each PBT particle that is not physically bonded to an Al2O3 particle is physically bonded to at least one other PBT particle. Such composite particles, and powders and pellets thereof, enable the formation of high ceramic content PBT-alumina molded articles by conventional processes such as compression molding and injection molding.
[0012] The present method of forming PBT-alumina composite particles enables the formation of a powder of such composite particles, where the PBT and alumina are substantially uniformly dispersed within the powder.
[0013] Ultimately, the method allows for the formation of a powder of PBT-alumina particles, where the powder has a relatively large percentage of ceramic (e.g., greater than 50% by volume, 50% to 90% by volume, 50% to 70% by volume, and / or the like).
[0014] As an example, such composite powders having a large proportion of structural ceramic (e.g., Al2O3) may be useful in structural components such as gears, CE housings, protective shields, etc., because these types of applications typically benefit from properties such as wear resistance, hardness, scratch resistance, toughness, and stiffness. Additionally, the inclusion of ceramic particles in a polymer matrix may allow for tailoring and / or selection of properties such as dielectric constant, dissipation factor, and RF transparency, which may be useful in certain electronics applications.
[0015] Certain configurations of the PBT-alumina composite powder include a plurality of composite particles, each of which includes an agglomerate of polybutylene terephthalate (PBT) particles physically bonded to a plurality of aluminum oxide (Al2O3) particles, at least some of the Al2O3 particles being exposed to the outer surface of the agglomerate of PBT particles, and the composite particles are in the form of a powder. The PBT-alumina composite particles may include 50% to 90% by volume of alumina and 10% to 50% by volume of PBT, and / or may have a Dv50 of 1 micrometer (μm) to 200 μm (e.g., 10 micrometers to 160 micrometers when unsieved, or 10 micrometers to 30 micrometers when sieved through a 15 micrometer mesh). Typically, substantially all of the PBT is uncrosslinked (e.g., 90% or more, 95% or more, 99% or more, or 99.9% or more). In some such configurations, the alumina particles may have a particle size (e.g., diameter or smallest transverse dimension) of 100 nanometers (nm) to 100 micrometers (μm), and / or less than 0.01 mm. 2 / g~20m 2 / g (e.g., 0.01 m 2 / g~10m 2 / g, 0.01m 2 / g~2m 2 / g).
[0016] The PBT-alumina composite powders can also be pelletized (converted to pellet form) to facilitate transportation, e.g., by limiting fines, and to facilitate subsequent molding. Such PBT-alumina materials in pellet form can include a plurality of solid pellets, each containing a plurality of the composite particles, where the PBT particles of adjacent composite particles are physically bonded to resist separation of adjacent composite particles and deformation of each pellet. As with the composite powders, typically substantially all of the PBT is not crosslinked (e.g., 90% or more, 95% or more, 99% or more, or 99.9% or more of the PBT).
[0017] In one particular implementation of the method of forming a ceramic-polymer composite powder, the method includes the steps of: mixing polybutylene terephthalate (PBT) particles, an organic solvent, and aluminum oxide (Al2O3) particles; at least partially dissolving the PBT particles with the solvent by heating the mixture to a first temperature between the glass transition temperature and the melting point of PBT while maintaining the mixture at a first pressure at which the solvent remains substantially liquid; stirring the heated mixture for several minutes while maintaining the mixture at or above the first pressure and at or above the first temperature but below the melting point of PBT; and cooling the mixture to a second temperature below a glass transition temperature of PBT or to a temperature less than the second temperature to (a) precipitate at least some of the PBT to form PBT particles, (b) agglomerate at least some of the PBT particles, and (c) bond at least some of the Al2O3 particles with the PBT particles, thereby forming a plurality of composite particles each comprising an agglomerate of polybutylene terephthalate (PBT) particles physically bonded with a plurality of aluminum oxide (Al2O3) particles, wherein at least some of the Al2O3 particles are exposed to an outer surface of the agglomerates of PBT particles.
[0018] In certain implementations of the method of molding a part from the PBT-alumina composite particles, the method includes subjecting a volume of the PBT-alumina powder or the PBT-alumina material in the form of pellets to a first pressure for several minutes while the PBT-alumina powder is at a first temperature above the melting point of PBT, such that the powder substantially fills a working portion of a mold cavity (e.g., fills 90% or more, 95% or more, 99% or more, or 99.9% or more of the working portion). In some such methods, the first pressure is sufficient to form a molded part with a relative density of greater than 90% (e.g., 97% or more) after the first pressure is applied to the powder for a period of at least 30 minutes.
[0019] Unless the disclosure expressly requires otherwise, the terms "a" and "an" are defined as one or more. The terms "substantially" and "about" are each defined generally, but not necessarily completely, as specified (and including what is specified, e.g., substantially 90 degrees includes 90 degrees), as would be understood by one of ordinary skill in the art. In any disclosed embodiment, the term "substantially" or "about" may be substituted with "within [percent]" of what is specified, which percentage includes .1, 1, 5, and 10 percent.
[0020] The phrase "and / or" means and, or. For purposes of illustration, A, B, and / or C includes A only, B only, C only, a combination of A and B, a combination of A and C, a combination of B and C, or a combination of A, B and C. In other words, "and / or" operates as an inclusive or. The phrase "at least one of A and B" has the same meaning as "A, B, or A and B."
[0021] Furthermore, a device or system configured in a certain way is configured in at least that way, but may be configured in another way than specifically described.
[0022] The terms "comprise" (and any form of comprise, such as "comprises" and "comprising"), "have" (and any form of have, such as "has" and "having"), and "include" (and any form of include, such as "includes" and "including") are open-ended linking verbs. As a result, an apparatus that "comprises," "has," or "includes" one or more elements has one or more elements, but is not limited to having only those one or more elements. Similarly, a method that "comprises," "has," or "includes" one or more steps has one or more steps, but is not limited to having only those one or more steps.
[0023] As used herein, the "size" or "diameter" of a particle refers to its equivalent diameter if the particle is shaped as a sphere, which is referred to herein as its diameter.The sphere shaped particle may be, for example, a sphere that has or produces a value measured for the particle, such as the mass and / or volume of the particle, the light scattered by the particle, etc.The particles of the present dispersion may be, but do not have to be, spherical.
[0024] Particle size and size distribution can be determined using known techniques, for example, laser diffraction, as described in the working examples below. Volumetric particle sizes "Dv90", "Dv50" and "Dv10" are defined as follows: "Dv50" corresponds to 50% of particles (by volume) that have a particle size smaller than a certain diameter. Dv50 is considered to be the average particle size of the volume distribution. "Dv90" and "Dv10" correspond to 90% and 10% of particles (by volume) that have a particle size smaller than a certain diameter, respectively.
[0025] Any aspect of any of the apparatus, systems, and methods may consist of, or consist essentially of, any described steps, elements, and / or features, rather than comprise / have / include any described steps, elements, and / or features. Thus, in any claim, the terms "consisting of" or "consisting essentially of" may be used in place of any of the open-ended linking verbs recited above to change the scope of a particular claim from one that is not otherwise defined using the open-ended linking verb.
[0026] One or more features of one embodiment may be applied to other embodiments even if not described or illustrated, unless expressly prevented by the content of this disclosure or the embodiment.
[0027] Some details relating to the aspects are set forth above, and other details are described below. [Brief description of the drawings]
[0028] The following drawings are illustrative and non-limiting. For the sake of brevity and clarity, not all features of a particular structure are always shown in all figures in which the structure appears. The same reference numerals do not necessarily indicate the same structure. Rather, the same reference numerals may be used to indicate similar features or features with similar functions, and non-identical reference numerals may be used to indicate similar features or features with similar functions.
[0029] [Figure 1] FIG. 1A is a schematic diagram of one of the present composite particles including a ceramic particle and a plurality of polymer particles, where the ceramic particles are larger than the respective polymer particles. FIG. 1B is a schematic diagram of one of the present composite particles including agglomerates of polymer particles and a plurality of ceramic particles, where the agglomerates of polymer particles are larger than the respective ceramic particles. [Diagram 2]FIG. 2 is a schematic diagram of the internal structure of a part molded from a dry powder of the composite particles. [Diagram 3] FIG. 3 is a flow chart of an example method for making a powder of the composite particles. [Figure 4] FIG. 4 is a schematic diagram of a stirred reactor of the type that can be used to make powders of the present composite particles. [Diagram 5] FIG. 5 is a flow chart of one example of a method for forming a part from a powder of the composite particles. [Figure 6] FIG. 6 is a schematic diagram of a compression mold for molding a part. [Figure 7] FIG. 7 is a scanning electron microscope (SEM) image of an example of the present PBT-alumina composite particles. [Figure 8] FIG. 8 is a scanning electron microscope (SEM) image of an example of the present PBT-alumina composite particles. [Figure 9] FIG. 9 is a scanning electron microscope (SEM) image of an example of the present PBT-alumina composite particles. [Figure 10] FIG. 10 is an SEM image of an example compression molded composite part made from example PBT-alumina composite particles. [Figure 11] FIG. 11 is an SEM image of an example compression molded composite part made from example PBT-alumina composite particles. [Figure 12] FIG. 12 is an SEM image of an example compression molded composite part made from example PBT-alumina composite particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] DETAILED DESCRIPTION OF ILLUSTRATIVE EMBODIMENTS Turning now to the drawings, and more particularly to FIG. 1A, a schematic diagram of one example of the present composite particle 10a is shown, which includes a ceramic particle 14a and a plurality of polymer particles 18a, 18b. The ceramic particle 14 includes aluminum oxide (Al2O3), and the polymer particles 18a, 18b include polybutylene terephthalate (PBT). As shown, four of the polymer particles 18a are physically associated with the ceramic particle 14a, and the remaining polymer particles 18b that are not physically associated with the ceramic particles are physically associated with one of the polymer particles 18a. In this example, the ceramic particle 14a is larger than the polymer particles 18a, 18b (e.g., has a minimum or maximum transverse dimension that is larger than the minimum or maximum transverse dimension of the polymer particles 18a, 18b, respectively).
[0031] FIG. 1B shows a schematic diagram of another example of the present composite particle 10b, which includes an agglomerate of polymer particles 18a and a plurality of ceramic particles 14a. Similar to particle 10a, ceramic particles 14b include aluminum oxide (Al2O3) and polymer particles 18 include polybutylene terephthalate (PBT). As shown, four ceramic particles 14b are physically associated with the agglomerate of polymer particles 18a. In this example, each individual ceramic particle 14b is comparable in size to each individual polymer particle 18a, but each individual ceramic particle 14b is smaller than the agglomerate of polymer particles (e.g., each ceramic particle 14b has a minimum or maximum transverse dimension that is smaller than each of the agglomerates of polymer particles). In other embodiments, at least some of the individual ceramic particles may be larger than at least some of the individual polymer particles. As shown here (and also shown in FIGS. 7-9), at least some of the ceramic particles are exposed to the exterior of the agglomerate of polymer particles (e.g., are not covered or substantially surrounded by the agglomerate of polymer particles). For example, two or more of the ceramic particles associated with the agglomerate of polymer particles may be exposed at the outer surface of the agglomerate. In some embodiments, the agglomerate of polymer particles may also surround one or more ceramic particles.
[0032] As explained in more detail below, the method allows for the formation of composite particles (eg, 10a, 10b) in which the polymer particles (eg, 18, 18a, 18b) are not crosslinked.
[0033] In the present composite particles, the ceramic particles (e.g., 14a, 14b) may have a particle size (e.g., diameter or smallest transverse dimension) of 100 nanometers (nm) to 100 micrometers (μm). For example, the ceramic particles used to form the present composite particles (e.g., by the methods described) may have a Dv90 or Dv50 of 100 nm to 100 μm (e.g., 100 nm to 500 nm, 100 nm to 400 nm, 1 μm to 100 μm, 1 μm to 50 μm, 2 μm to 50 μm, 3 μm to 20 μm, 2 μm to 10 μm, 3 μm to 10 μm, 4 μm to 10 μm). Additionally or alternatively, the ceramic particles may have a particle size (e.g., diameter or smallest transverse dimension) of 0.01 nm to 100 μm. 2 / g~20m 2 / g (e.g., 0.01 m 2 / g~10m 2 / g, 0.01m 2 / g~2m 2 / g).
[0034] The composite particles (e.g., 10a, 10b) may have a particle size (e.g., diameter or smallest transverse dimension) of 1 micrometer (μm) to 200 micrometers (μm) or may be configured to have a particle size (e.g., diameter or smallest transverse dimension) of 1 micrometer (μm) to 200 micrometers (μm). For example, the composite particles may have a Dv90 or Dv50 of 1 μm to 200 μm (e.g., 1 μm to 50 μm, 1 μm to 10 μm, 100 μm to 200 μm, or 125 μm to 175 μm).
[0035] The powder includes a plurality of particles (e.g., 10a, 10b), e.g., in the form of a powder. For example, the powder may be characterized by a polymer-solvent content (solvent in which the polymer is soluble) of less than 3,000 parts per million (ppm) (e.g., less than 2,000 ppm, less than 1,000 ppm). However, in some configurations, the powder may be mixed with and / or suspended in a non-polymer-solvent liquid (liquid in which the polymer does not dissolve), such as water. In such configurations, the liquid may inhibit and / or prevent the particles from becoming airborne or respirable, e.g., for transport and handling of fine powders. In at least some configurations of the powder, the powder is free-flowing ff c has at least one (e.g., 1-8, 1-6, 1-4, 2-4) flow form, and in some configurations has a flow form without a flow promoter.
[0036] In some configurations of such powders, the composite particles in the agglomerate comprise between 50% and 90% by volume ceramic (eg, between 50% and 70% by volume ceramic).
[0037] FIG. 2 is a schematic diagram of the internal structure of a molded part made from a dry powder of the present composite particles (e.g., 10a, 10b). As shown, the polymer particles (e.g., 18, 18a, 18b) of adjacent composite particles coalesce to fill the gaps between the ceramic particles and bond them together to form the molded ceramic-polymer composite. As shown, a relatively large percentage of ceramic in the powder (e.g., 50% to 90% by volume) means that a correspondingly large percentage of the molded part is also ceramic. Furthermore, the use of the present composite particles, in which the polymer particles are physically bonded to the ceramic particles within the multiple individual composite particles prior to molding, results in a more uniform polymer distribution within the matrix of the molded part.
[0038] The powder can be pelletized or bonded into pellet form with adjacent composite particles of polymer particles bonded together to resist separation of adjacent composite particles and deformation of each pellet. For example, the powder can be subjected to high temperatures and pressures in an extruder. Such temperatures are above the glass transition temperature (T) of the polymer in the PBT-alumina composite particles so as to make the PBT sticky but not liquefied. g ) or near the surroundings. Such pressure (e.g., during extrusion) may be elevated relative to the surroundings such that the polymer particles of adjacent composite particles are bonded sufficiently to resist separation, but not so much that the independent boundaries / identities of adjacent polymer particles are lost. In such a configuration, the pellet form may facilitate transportation of the composite particles (e.g., for distribution). Such pelletization may be accomplished by any of a variety of methods and processes known in the art, such as, for example, a screw extruder.
[0039] Polybutylene terephthalate (PBT) Polybutylene terephthalate (PBT) is a semi-crystalline engineering thermoplastic material used, for example, as an electrical insulator. Various grades of PBT are commercially available, including, for example, VALOX™ Resin and VALOX™ FR Resin available from SABIC Innovative Plastics. IQ PBT or VALOX 195 particles from SABIC Thermoplastics were used in this example. In other implementations, other PBT grades (e.g., IQ PBT or VALOX 315) or mixtures of different PBT grades (e.g., mixtures of IQ PBT / VALOX 195 and IQ PBT / VALOX 315) can be used.
[0040] Method for preparing powder of PBT-Al2O3 composite particles Turning now to Figures 3 and 4, Figure 3 illustrates a flow chart 20 of an example method for making powders of the present composite particles (e.g., 10a, 10b), and Figure 4 illustrates a schematic diagram of an agitated reactor 34 (e.g., a PARR™ reactor or an R-2004 reactor) of a type that can be used to make powders of the present composite particles.
[0041] The step of initially mixing the ceramic particles with a solvent may have certain benefits, for example, in reducing agglomeration of the ceramic particles. This benefit can be realized whether starting with non-agglomerated ceramic particles in powder form or with agglomerated ceramic particles in powder form. For example, the Al2O3 powder (CL3000FG) used in the examples below was obtained from Almatis GmbH and, in its raw form prior to use in the method, had an average particle size (D50) of 4.2 micrometers (μm), a particle size of 3.6 μm to 4.8 μm, and a surface area of 0.75 to 1.20 m. 2 / g (typical 0.90m 2 The ceramic particles consisted of finely ground alumina particles at 1000g / g. In some cases, mixing the ceramic particles with a solvent before adding the PBT particles can reduce agglomeration before mixing with the PBT particles, and can also be used to resist reagglomeration of the ceramic particles during subsequent addition to the PBT and bonding.
[0042] In step 22, the PBT particles, the solvent, and the ceramic particles are mixed together. The PBT particles, the solvent, and the ceramic may be mixed simultaneously in one vessel (e.g., directly in the shell or vessel 36 of the stirred reactor 34) or sequentially. For example, the ceramic particles may be added to the solvent first (e.g., in a first vessel such as a homogenizer), and then the PBT particles may be added to the solvent-ceramic mixture (e.g., in a first vessel such as the shell or vessel 36 of the stirred reactor 34 or in a second vessel). The solvent may include any solvent in which the PBT particles partially dissolve under heating conditions, as described below. Other solvents that may be utilized in the present method include those in which PBT is freely soluble or sparingly soluble at elevated temperatures (e.g., above 75° C., above 100° C., about 150° C., and / or above 200° C.), as well as those in which PBT is slightly soluble or sparingly soluble at lower temperatures (e.g., below 50° C., e.g., ambient temperature). Examples of such solvents include relatively non-polar solvents having boiling points above 100° C. (e.g., above 150° C.), such as methoxybenzene, orthodichlorobenzene (ODCB), chlorobenzene, dichlorotoluene, 1,2,4-trichlorobenzene, diphenyl sulfone, monoalkoxybenzenes (e.g., anisole, veratrole, diphenyl ether, or phenetole), and other solvents in which PBT is soluble or sparingly soluble at elevated temperatures (e.g., above 75° C., above 100° C., about 150° C., and / or above 200° C.) and sparingly soluble or sparingly soluble at lower temperatures (e.g., below 50° C., e.g., ambient temperature). As used in the preceding sentence, freely soluble means that 1-10 ml of solvent is required to dissolve 1 gram (g) of PBT, slightly soluble means that 10-30 ml of solvent is required to dissolve 1 gram (g) of PBT, sparingly soluble means that 100-1000 ml of solvent is required to dissolve 1 gram (g) of PBT, and slightly soluble means that 1000-10000 ml of solvent is required to dissolve 1 gram (g) of PBT.Further examples of solvents suitable for carrying out at least a portion of the present method include polar aprotic solvents (e.g., dimethylformamide (DMF), dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), sulfolane, and N-methylpyrrolidinone (NMP)); and ketones (e.g., cyclohexanone, cyclopentanone, methyl ethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, and diisobutyl ketone).
[0043] In step 24, the mixture of PBT particles, ceramic particles, and solvent is heated (e.g., by heating element 38 of reactor 34) to partially dissolve the PBT with the solvent. In particular, the mixture is heated to a first temperature (e.g., a temperature at or below the normal boiling point of the solvent) above the glass transition temperature of PBT but below the melting temperature of PBT under a first pressure at which the solvent remains liquid. For example, using ODCB and T m When using PBT at 225°C, the mixture can be heated to 180°C under a pressure of 10 pounds per square inch (psi) or more (e.g., 70 psi). When using other solvents, the pressure may be kept at a different level (e.g., 100 psi).
[0044] In step 26, which may be performed partially or completely simultaneously with step 24, the mixture is agitated (e.g., by impeller 162 of reactor 34) for a number of minutes (e.g., for or greater than 1, 5, 10, 20, 30, 40, 50, 60, or more minutes) while substantially maintaining the temperature of the mixture at or above the first temperature and while substantially maintaining the pressure to which the mixture is subjected at or above the first pressure. In particular, the temperature and pressure are maintained during agitation so as to keep the mixture heated.
[0045] In step 28, the mixture is cooled to a second temperature below the glass transition temperature of PBT or to a temperature below the second temperature to (a) precipitate at least some of the PBT to form PBT particles, (b) agglomerate at least some of the PBT particles, and (c) bond at least some of the Al2O3 particles to the PBT particles, thereby forming a plurality of composite particles each including an agglomerate of polybutylene terephthalate (PBT) particles physically bonded with a plurality of aluminum oxide (Al2O3) particles, with at least some of the Al2O3 particles exposed to the outer surface of the agglomerate of PBT particles. For example, the mixture may be cooled to less than 55°C, less than 55°C, and / or less than 35°C. Optionally, the mixture may be kept stirred during this cooling step to resist agglomeration of the composite particles.
[0046] In an optional step 30, the formed composite particles may be washed or rinsed with the same solvent (e.g., ODCB) added in step 22 or with a different solvent (e.g., methanol). For example, the wet solid cake may be removed from the vessel (e.g., the shell of reactor 34 or vessel 36) and placed in a filter for rinsing.
[0047] In step 32, the solid cake is dried, for example, at a temperature above the normal boiling point of the solvent added in step 22 and / or the normal boiling point of the solvent used to wash / rinse the solid cake in optional step 30, optionally at a second pressure lower than ambient pressure (i.e., under reduced pressure) to form a dry powder of composite particles (e.g., 10). For example, when ODCB (normal boiling point of about 180° C.) is added in step 22 and methanol (normal boiling point of about 65° C.) is used in step 30, the solid cake can be dried under reduced pressure at a temperature of 120° C. for a period of time (e.g., 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 18 hours, or more).
[0048] Method for forming parts from PBT-Al2O3 composite particle powders 5 and 6, Figure 5 illustrates a flow chart 40 of an example method for molding a part from a powder of the present composite particles. Figure 6 illustrates a schematic 250 of a compression mold for molding the part.
[0049] In step 41, a working portion of cavity 47 in mold 48 is filled with a powder 49 of the present composite particles (eg, 10).
[0050] In step 42, the powder (49) is heated to a temperature below the melting temperature of PBT (T m ) (e.g., by heating jacket 50) to a first temperature that exceeds (e.g., at least 10° C., at least 20° C., at least 30° C., or more) or to a temperature that is greater than the first temperature. For example, the T m may be about 195° C. and the first temperature may be 225° C. Similarly, T m For PBT with a melting point of 223°C, the first temperature may be 250°C.
[0051] In step 43, which may be performed partially or completely simultaneously with step 42, the powder is subjected to a first pressure (e.g., 370 megapascals (MPa)) in the mold while the powder (e.g., and mold) is maintained at or above the first temperature. The pressure may be maintained for several minutes (e.g., equal to or greater than 5, 10, 20, 30, 40, 50, 60, or more minutes). In some implementations, the conditions (temperature, pressure, etc.) and the period of time the conditions are maintained are sufficient to result in a molded article with a relative density of greater than 90%.
[0052] additives Any of the present powders may be mixed with or otherwise formed to include one or more additives. For example, after one of the present powders is formed, one or more additives may be mixed with it before or after drying such that the additive (e.g., particles of the additive) are mixed or dispersed (e.g., uniformly) throughout the volume of the powder. In certain instances, one or more additives are mixed with the dry powder just prior to adding the powder to the mold to affect the formation (e.g., color and / or other physical properties) of the part to be molded.
[0053] The additive(s) may include any of the various additives typically incorporated into such polymers, provided that the additives are selected so as not to adversely affect the desired properties of the powder itself, or of the molded article, if applicable. Examples of such additives include fillers, reinforcing agents, antioxidants, heat stabilizers, light stabilizers, ultraviolet (UV) light stabilizers, plasticizers, lubricants, mold release agents, antistatic agents, colorants, e.g., titanium dioxide, carbon black, organic pigments, surface effect additives, radiation stabilizers, additional flame retardants, and anti-drip agents. In general, additives are used in amounts generally known to be effective. For example, the total amount of additives (other than fillers or reinforcing agents) may be 0.01 to 25 parts by weight per 100 parts by weight (PHR) of polymer, as the case may be.
[0054] Coloring agent The one or more additives may include one or more colorants, such as pigments or dyes. Examples of pigments include, for example, inorganic pigments, such as metal oxides and mixed metal oxides, such as zinc oxide, titanium dioxide, iron oxide, and the like; sulfides, such as zinc sulfide, and the like; aluminates; sodium sulfo-silicates; sulfates), sulfuric acid, chromate, and the like; carbon black; zinc ferrite; ultramarine blue; organic pigments such as azo, diazo, quinacridone, perylene, naphthalenetetracarboxylic acid, flavanthrone, isoindolinone, tetrachloroisoindolinone, anthraquinone, enthrone, dioxazine, phthalocyanine, and azo lakes; Pigment Red 101, Pigment Red 122, Pigment Red 149, Pigment Red 177, Pigment Red 179, Pigment Red 202, Pigment Violet 29, Pigment Blue 15, Pigment Blue 60, Pigment Green 7, Pigment Yellow 119, Pigment Yellow 147, Pigment Yellow 150, and Pigment Brown 24; or combinations of any such pigments. Pigments such as titanium dioxide can result in commercially desirable white compositions. Pigments such as titanium dioxide (or other mineral fillers) may be present in the thermoplastic composition in an amount of 0 to 12 PHR, 0.1 to 9 PHR, 0.5 to 5 PHR, or 0.5 to 3 PHR.
[0055] Dyes are generally organic materials and include coumarin dyes, such as coumarin 460 (blue), coumarin 6 (green), Nile Red, etc.; lanthanide complexes; hydrocarbon and substituted hydrocarbon dyes; polycyclic aromatic hydrocarbon dyes; scintillation dyes, such as oxazole or oxadiazole dyes; aryl or heteroaryl substituted poly(C2-8) olefin dyes; carbocyanine dyes; indanthrone dyes; phthalocyanine dyes; oxazine dyes; carbostyril dyes; napthalenetetracarboxylic acid acid dyes;porphyrin dyes;bis(styryl)biphenyl dyes;acridine dyes;anthraquinone dyes;cyanine dyes;methine dyes;arylmethane dyes;azo dyes;indigoid dyes, thioindigoid dyes, diazonium dyes;nitro dyes;quinoneimine dyes;aminoketone dyes;tetrazolium dyes;thiazole dyes;perylene dyes, perinone dyes;bis-benzoxazolylthiophene (BBOT);triarylmethane dyes;xanthene dyes;thioxanthene dyes;naphthalimide dyes;lactone dyes;fluorophores, such as anti-Stokes shift dyes that absorb in the near infrared wavelengths and emit in the visible wavelengths;luminescent dyes, such as 7-amino-4-methylcoumarin;3-(2'-benzothiazolyl)-7-dimethyl Aminocoumarin;2-(4-biphenylyl)-5-(4-t-butylphenyl)-1,3,4-oxadiazole;2,5-Bis-(4-biphenylyl)-oxazole;2,2'-Dimethyl-p-quaterphenyl;2,2-Dimethyl-p-terphenyl;3,5,3'''',5''''-Tetra-t-butyl-p-quinquiphenyl;2,5-Diphenylfuran;2,5-Diphenyloxazo 4,4'-Diphenylstilbene;4-Dicyanomethylene-2-methyl-6-(p-dimethylaminostyryl)-4H-pyran;1,1'-Diethyl-2,2'-carbocyanine iodide;3,3'-Diethyl-4,4',5,5'-dibenzothiatricarbocyanine iodide;7-Dimethylamino-1-methyl-4-methoxy-8-azaquinolone-2;7-Dimethylamino-4-methylquinolone-2;2-(4-(4-dimethylaminophenyl)-1,3-butadienyl)-3-ethylbenzothiazolium perchlorate; 3-diethylamino-7-diethyliminophenoxazonium perchlorate; 2-(1-naphthyl)-5-phenyloxazole; 2,2'-p-phenylene-bis(5-phenyloxazole); rhodamine 700; rhodamine 800; pyrene, chrysene, rubrene, coronene, and the like; monoazo and disazo dyes; and combinations comprising at least one of the foregoing dyes and / or pigments. Colorants are generally used in amounts of 0.01 to 20 PHR, excluding any fillers. For at least some implementations, colorants that do not fade from polymer melts above 300C are preferred, as are colorants having molecular weights above 500 Daltons.;
[0056] antioxidants The one or more additives may include one or more antioxidants. Examples of antioxidant additives include organophosphites, such as tris(nonylphenyl)phosphite, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, distearyl pentaerythritol diphosphite; alkylated monophenols or polyphenols; alkylation reaction products of polyphenols and dienes, such as tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane; butylation reaction products of para-cresol or dicyclopentadiene; alkylated hydroquinones; hydroxylated thiodiphenyl ethers; alkylidene-bisphenols; benzyl compounds; β-(3,5-di-tert-butyl-4-hydroxyfuran); esters of β-(5-tert-butyl-4-hydroxy-3-methylphenyl)-propionic acid with monohydric or polyhydric alcohols; esters of thioalkyl or thioaryl compounds, such as distearyl thiopropionate, dilauryl thiopropionate, ditridecyl thiodipropionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythrityl-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; amides of β-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, or combinations comprising at least one of the foregoing antioxidants. The antioxidants are used in amounts of 0.01 to 0.1 PHR.
[0057] Heat stabilizer The one or more additives may include one or more heat stabilizers. Examples of heat stabilizer additives include organophosphites, such as triphenyl phosphite, tris-(2,6-dimethylphenyl) phosphite, and tris-(mixed mono- and di-nonylphenyl) phosphite; phosphonates, such as dimethylbenzene phosphonate; phosphates, such as trimethyl phosphate; or a combination comprising at least one of the aforementioned heat stabilizers. Heat stabilizers are used in some implementations in an amount of 0.01 to 0.1 PHR.
[0058] Light stabilizers and ultraviolet (UV) light stabilizers The one or more additives may include one or more light stabilizers and / or one or more UV absorbing additives. Examples of light stabilizer additives include benzotriazoles, such as 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)-benzotriazole and 2-hydroxy-4-n-octoxybenzophenone, or a combination comprising at least one of the aforementioned light stabilizers. The light stabilizer is used in an amount of 0.01 to 5 PHR in some implementations.
[0059] Examples of UV absorbing additives include hydroxybenzophenones; hydroxybenzotriazoles; hydroxybenzotriazines; cyanoacrylates; oxanilides; benzoxazinones; 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)-phenol (CYASORB® 5411); 2-hydroxy-4-n-octyloxybenzophenone (CYASORB® 531); 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-(octyloxy)-phenol (CYASORB® 1164); 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one) (CYASORB® UV- 3638); 1,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl]propane (UVINUL® 3030); 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazin-4-one); 1,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[[(2-cyano-3,3-diphenylacryloyl)oxy]methyl]propane; nano-sized inorganic materials, such as titanium oxide, cerium oxide, and zinc oxide, all having a particle size less than or equal to 100 nanometers; or a combination comprising at least one of the foregoing UV absorbers. The UV absorber is used in some implementations in an amount of 0.01 to 5 PHR.
[0060] Plasticizers, lubricants, and / or release agents The additive(s) may include one or more plasticizers, one or more lubricants, and / or one or more mold release agents. There is considerable overlap between these types of materials. Examples include phthalates, such as dioctyl-4,5-epoxy-hexahydrophthalate; tris-(octoxycarbonylethyl)isocyanurate; tristearin; poly-α-olefins; epoxidized soybean oil; silicones, including silicone oils; esters, such as fatty acid esters, such as alkylstearyl esters, such as methyl stearate, stearyl stearate, pentaerythritol tetrastearate, and the like; combinations of hydrophilic and hydrophobic nonionic surfactants, including methyl stearate and polyethylene glycol polymers, polypropylene glycol polymers, poly(ethylene glycol-co-propylene glycol) copolymers, or combinations comprising at least one of the aforementioned glycol polymers, such as methyl stearate and polyethylene-polypropylene glycol copolymers dissolved in a solvent; waxes, such as beeswax, montan wax, and paraffin wax. Such materials are used in amounts of 0.1 to 1 PHR in some implementations.
[0061] Flame retardants The one or more additives may include one or more flame retardants. Examples of flame retardants include salts of C1-16 alkylsulfonic acids, such as potassium perfluorobutanesulfonate (Rimar salt), potassium perfluorooctane sulfonate (KSS), tetraethylammonium perfluorohexanesulfonate, and potassium diphenylsulfonesulfonate; salts such as Na2CO3, K2CO3, MgCO3, CaCO3, and BaCO3, inorganic phosphates, and fluoro-anion complexes such as Li3AlF6, BaSiF6, KBF4, K3AlF6, KAlF4, K2SiF6, and / or Na3AlF6. Organic flame retardants can be used in some implementations, but in some such implementations, halogenated flame retardants may be avoided so that the thermoplastic composition is essentially free of chlorine and bromine. As used herein, "essentially free of chlorine and bromine" means having a bromine and / or chlorine content of less than or equal to 100 parts per million (ppm) by weight, less than or equal to 75 ppm, or less than or equal to 50 ppm, based on the total weight parts of the composition, excluding any fillers.
[0062] Drip-proofing agent EXAMPLES
[0063] 1. Example 1: 40:60 powder of PBT-Al2O3 composite particles material: 1642 grams (g) alumina (Al2O3), 358 g PBT, 17.94 kg ODCB. The PBT was IQ PBT 195 particles from SABIC Thermoplastics, and the alumina particles were CL3000FG Al2O3 particles from Almatis GmbH. The relative amounts of alumina and PBT resulted in approximately 60 volume percent alumina of the composite particles formed.
[0064] procedure: At room temperature and ambient pressure, ODCB was added to the R-2004 reactor. The agitator of the R-2004 reactor was then turned on at 100 rpm. With the agitator running, PBT was then added to the reactor through a funnel through the sight glass opening, followed by alumina through the same funnel through the sight glass opening. A small amount (0.2 kg) of ODCB was then used to rinse the funnel into the sight glass opening to ensure that all residues of PBT (e.g., remaining monomer) were inside the reactor chamber. A line from a nitrogen (N2) supply was then attached to the headspace port of the reactor shell, and the headspace inside the shell was purged with N2 several times. It was observed that the pressure inside the reactor shell during the purging process ensured a tight seal. Specifically, N2 was added to pressurize the reactor chamber to 30 pounds per square inch gauge (psig). Thus, once N2 was added to the headspace, the N2 source was turned off and all valves on the PARR™ reactor were closed. When the pressure remained substantially constant (less than 1 psig decrease) after approximately 15 minutes, the pressure was released and the headspace was purged with N2 a total of five times, each time pressurizing the reactor chamber to 30 psig. If the pressure instead decreased, the pressure was released, the unit was re-tightened, and the process was repeated until the pressure was constant, after which the headspace could be purged a total of five times. After this purging process, N2 delivery to the headspace was maintained at a rate of 5 standard cubic feet per hour (scfh).
[0065] The reactor vessel was then heated and when the temperature reached approximately 100°C, the three-way overhead valve was closed and the nitrogen purge was discontinued. Heating was continued until the vessel reached the target temperature of 180°C. A target temperature of 80°C and a pressure in the reactor chamber of 10 psig were maintained for a period of 30 minutes while continuing to stir. After 30 minutes, the heater was turned off and the mixture was cooled to a temperature of approximately 30°C to ensure that all the PBT had precipitated. The Nutsche filter valve of the reactor was then opened and N2 was delivered to the reactor chamber at 40 psig to direct the reactor contents to a Nutsche filter equipped with a 0.7 micron (micrometer or μm) filter on top of a 20 micron (micrometer or μm) filter. All of the reactor contents were transferred to the filtrate receiver of the Nutsche filter, the pressure in the reactor chamber was reduced, and the agitator was turned off. The side walls of the reactor were rinsed with approximately 2 kg of ODCB, which was then transferred to the filter receiver.
[0066] The feed and vent valves for the filter were then closed and the filter was pressurized to 40 psig to dry the cake of composite PBT-alumina particles until nitrogen passed through the cake. The pressure was then released from the Nutsche filter. The cake in the Nutsche filter was then washed with methanol at 40 psig pressure, after which the pressure was reduced and the methanol was removed, after which the cake was dried with a stream of nitrogen for a period of 30 minutes. The cake was then removed from the Nutsche filter and placed in an aluminum dish and dried under vacuum (25-30 mm at 80° C. for a period of 18 hours). FIG. 7 illustrates the 40:60 PBT-alumina composite particles formed. Certain properties of the resulting dried powder of 40:60 PBT-Al2O3 composite particles were then measured and are listed in Tables 1 and 2 below.
[0067] 2. Example 2: 50:50 powder of PBT-Al2O3 composite particles material: 1508 grams (g) alumina (Al2O3), 492 g PBT, 17.94 kg ODCB. The relative amounts of alumina and PBT resulted in approximately 50 volume percent alumina of the composite particles formed.
[0068] procedure: The procedure for this Example 2 was substantially the same as that described above for Example 1. Figure 8 illustrates the 50:50 PBT-alumina composite particles that were formed. Certain properties of the resulting dry powder of 50:50 PBT-alumina particles were then measured and are listed below in Tables 1 and 2.
[0069] 3. Example 3: 60:40 powder of PBT-Al2O3 composite particles material: 1342 grams (g) alumina (Al2O3), 658 g PBT, 17.94 kg. The relative amounts of alumina and PBT resulted in approximately 40 volume percent alumina of the composite particles formed.
[0070] procedure: The procedure for this Example 3 was substantially the same as that described above for Example 1. Figure 9 illustrates the 60:40 PBT-alumina composite particles that were formed. Certain properties of the resulting dry powder of 60:40 PBT-alumina particles were then measured and are listed below in Tables 1 and 2.
[0071] 4. Example 4: Compression molded pellets of 40:60 PBT-Al2O3 composite particles. material: 1.2 g dry powder of 40:60 PBT-Al2O3 composite particles produced in Example 1 above.
[0072] procedure: The powder was placed in an aluminum pan and measured. The powder was then poured into a cylindrical mold with an inside diameter of 13 millimeters (mm) using a paper funnel. The powder was then lightly compacted in the mold using a rod and a heating jacket was attached around the mold. The mold was then heated to a first temperature of 225° C. and maintained at the first temperature for five (5) minutes. A hydraulic press was then used to apply a pressure of 5 tons or 370 MPa to the powder. The mold was then held at the first temperature and the powder was under pressure for a period of five (5) minutes after which the heater was turned off and the mold was allowed to cool while maintaining the pressure. After a total of 30 minutes (starting with 5 minutes of uncompressed heating), the PBT-alumina composite pellet was removed from the mold, the pellet was weighed, its dimensions were measured and the relative density was calculated. FIG. 10 illustrates the microstructure of the compressed pellets of this Example 4. Certain characteristics of the pellets are set forth in Table 3 below.
[0073] 5. Example 5: Compression Molded Pellets of 50:50 PBT-Al2O3 Composite Particles material: 1.2 g dry powder of 50:50 PBT-Al2O3 composite particles produced in Example 2 above.
[0074] procedure: The procedure for this Example 5 was substantially the same as that described above for Example 4. Figure 11 illustrates the microstructure of the compressed pellets of this Example 5. Certain characteristics of the pellets are listed in Table 3 below.
[0075] 6. Example 6: Compression Molded Pellets of 60:40 PBT-Al2O3 Composite Particles
[0076] Materials: 1.2 g dry powder of 60:40 PBT-Al2O3 composite particles produced in Example 3 above.
[0077] procedure: The procedure for this Example 6 was substantially the same as that of Example 4. Figure 12 illustrates the microstructure of the compressed pellets of this Example 6. Certain characteristics of the pellets are listed in Table 3 below.
[0078] 7. Experimental Results Various combinations of composite particle powders were produced as described above for certain examples, with certain processing parameters and powder properties listed in Table 1. The PBT reference powder, labeled "PBT Reference" in Table 1, was made by a process similar to that described above for Example 1, except that no ceramic particles were included in the mixture, and IQ PBT 195 particles (SABIC Thermoplastics) were included at 10% by volume in the ODCB solvent. The particle size of the Al2O3 powder (labeled "Al2O3" in Table 1) was also measured.
[0079] Table 1A: Powder production - process parameters TIFF2025505570000002.tif42166
[0080] Table 1B: Powder production - parameters of unsieved powder TIFF2025505570000003.tif33166
[0081] Table 1C: Powder production - sieved powder parameters (150 μm mesh) TIFF2025505570000004.tif29166
[0082] Table 1D. Powder production by heating-cooling process - Powder parameters TIFF2025505570000005.tif29128
[0083] The particle size values of the powders were measured using a commercial particle size analyzer (available from Malvern Panalytical Ltd., Malvern, UK).
[0084] Particle morphology was also examined using scanning electron microscopy. Figures 7, 8, and 9 show 40:60, 50:50, and 60:40 PBT-alumina particles, respectively. Figures 10, 11, and 12 show the microstructures of 40:60, 50:50, and 60:40 PBT-alumina particles, respectively, pressed into parts. Alumina particles bound to the agglomerates of PBT particles are evident on the composite powder in Figures 7, 8, and 9, such that at least some of the alumina particles are exposed on the outer surface of each PBT agglomerate. Thin layers of PBT are also evident between the ceramic grains in Figures 10, 11, and 12.
[0085] The thermogravimetric analysis (TGA) and molecular weight (measured by GPC) properties of the PBT-alumina composite powders of Example 1 described above are summarized in Table 2. In addition, certain TGA and molecular weight properties were determined for each of the composite powder components). The density and molecular weight of each powder are provided for comparison reference. No obvious degradation of polymer molecular weight was observed from this heating-cooling method of making the composite particles.
[0086] Table 2. Density, TGA, and molecular weight data for composite powders TIFF2025505570000006.tif32130
[0087] The TGA and molecular weight (measured by GPC) results for compression molded parts made from the PBT-alumina composite powder are summarized in Table 3. The density and molecular weight of polymer parts molded under the same conditions as in Table 2 are shown for comparison.
[0088] Table 3A. Pellet characteristics of composite powders TIFF2025505570000007.tif32144
[0089] Table 3B. Pellet characteristics of composite powders TIFF2025505570000008.tif32128
[0090] The relative density is the density of the molded pellets (density measurement (ρ M )) and comparing it to the theoretical density. Density measurements can be calculated by weighing the pellets (measured using a balance or scale) and dividing by the volume determined by measuring the outer dimensions (volumes of other shapes can be determined by any of a variety of known methods, for example, by submerging in an incompressible fluid). In this example, density measurements of the samples (e.g., pellets) were determined by Archimedes' method using a KERN ABS-N / ABJ-NM balance equipped with an ACS-A03 density measurement set. In particular, each sample was dried and the dry weight (W dry The specimen was then boiled in water for an hour so that all voids in the object were filled with water. The specimen was then suspended in the used liquid at a known (non-boiling) temperature and the apparent mass (W sus The sample was then removed from the water and excess water was wiped off the surface of the sample using a tissue paper moistened with water. The fully saturated sample was then immediately weighed in air (W sat The density is then calculated using Equation (2): Calculated using TIFF2025505570000009.tif7128.
[0091] In this example, the amount of polymer and ceramic in the pellets was known. When the starting proportions are unknown, the organic content of the polymer in the compression molded pellets can be determined by thermogravimetric analysis (TGA) in air. This allows the calculation of the ceramic content in the compression molded pellets. The combined or theoretical density (ρ T ) into equation (3): Calculations were performed using TIFF2025505570000010.tif5128. In the formula, m p is the mass of polymer in the molded pellet, and ρ p is the density of the polymer, and m c is the mass of ceramic in the molded pellet, and ρ cis the density of the ceramic. Then, the relative density (ρ R ) into equation (4): Calculate according to TIFF2025505570000011.tif5128.
[0092] Weight change measurements can be programmed as isothermal or linear heating temperature conditions and monitored in solid or liquid specimens using a Thermogravimetric Analyzer (TGA). Weight change, usually weight loss, measurements can be attributed to decomposition (thermal or oxidative) of the specimen with release of volatiles below the decomposition temperature of the sample. For the TGA measurements discussed herein, less than 50 mg of sample was weighed into a platinum pan and TGA testing was performed in air at a heating rate of 20° C. / min using a Discovery TGA.
[0093] Thermal analysis was performed by Differential Scanning Calorimetry (DSC), a method that measures heat flow and thermal transitions of samples (e.g., polymers, monomers, and additives) as a function of temperature according to a predetermined time and temperature program. These thermal transitions are measured during heating, cooling, or isothermal cycles. These transitions occur when a material undergoes a physical or chemical change. DSC was performed on a TA-Q1000 Analyzer at 20 C / min.
[0094] The molecular weight measurements reported in Tables 2 and 3 above and Table 4 below were determined by liquid chromatography using an Agilent 1260 Infinity II HPLC (available from Agilent Technologies, Inc., Santa Clara, Calif., USA) equipped with an isocratic pump, a vial sampler, a multi-column thermostat (MCT) for controlling the temperature of the mobile phase passing through the column, and a variable wavelength detector (VWD). The system was controlled by Agilent GPC / SEC software, and measurements were performed using known methods.
[0095] Weight change measurements can be programmed as isothermal or linear heating temperature conditions and monitored in solid or liquid specimens using a Thermogravimetric Analyzer (TGA). Measurements of weight change, usually weight loss, can be attributed to decomposition (thermal or oxidative) of the specimen with release of volatiles below the decomposition temperature of the sample. For the TGA measurements discussed herein, less than 50 mg of sample was weighed into a platinum pan and TGA testing was performed in air at a heating rate of 20°C / min using a Discovery TGA.
[0096] Thermal analysis was performed by Differential Scanning Calorimetry (DSC), a method that measures heat flow and thermal transitions of samples (e.g., polymers, monomers, and additives) as a function of temperature according to a predetermined time and temperature program. These thermal transitions are measured during heating, cooling, or isothermal cycles. These transitions occur when a material undergoes a physical or chemical change. DSC was performed on a TA-Q1000 Analyzer at 20 C / min.
[0097] Rectangular beams were also cut using a CNC mill from the 35 mm pellets produced above for Examples 4, 5, and 6 to determine certain mechanical properties. In particular, the beams were cut to have a rectangular cross section of approximately 4 mm x 3 mm, polished using 600 grit sandpaper, and tested in three-point bending at a displacement rate of 1 mm / min. Table 4 summarizes the measured properties and reference properties for Al2O3 only available in the literature.
[0098] (Table 4) Mechanical properties of compression molded products TIFF2025505570000012.tif35160
[0099] In addition to the mechanical properties reflected in Table 4 for Examples 4, 5, and 6, additional molded parts were formed using a similar process as described above for Example 4, but starting with similar 40:60, 50:50, and 60:40 volume ratio dry mixtures of IQ PBT 195 PBT particles and CL3000FG alumina particles. In these comparative examples, the dry PBT particles were mechanically mixed with the dry alumina particles for 6 minutes using a Harbil 5G shaker. The resulting molded disks were then subjected to the same tests to measure flexural modulus, flexural strength, and flexural strain. The molded parts formed from the composite powders showed predictable mechanical property changes between the 40:60, 50:50, and 60:40 PBT-alumina volume ratios, indicating a substantially uniform distribution of the PBT and alumina particles. In contrast, parts formed from dry mixed powders exhibited inconsistent mechanical properties among the 40:60, 50:50, and 60:40 PBT-alumina volume ratios, indicating a non-uniform distribution of PBT and alumina particles.
[0100] In addition to the mechanical properties listed in Table 4, the dielectric constant (dk) and dissipation factor (df) were also measured at 100 MHz, 500 MHz, and 1 GHz for 35 mm disks with thicknesses less than 1.01 mm. Table 5 summarizes the measured properties and Al2O3-only reference properties obtained in the literature.
[0101] The dielectric permittivity (Dk) and loss tangent or dissipation factor (Df) at different frequencies were determined using the parallel plate configuration and split-post dielectric resonator (SPDR) as specified in ASTM D150 or IPC 2.5.5.9 using the test method defined in IEC (International Electrotechnical Commission) standard 61189-2-721 (Ed. 1.0 b:2015). In particular, the parallel plate measurements (ASTM D150) at 1 MHz were facilitated by a 16541B test fixture and an E4980AL LCR meter (Keysight). The experimental setup included a network analyzer (Agilent Technologies E5071C) connected to the SPDR device of choice.
[0102] The reported Dk and Df values are the average of five measurements with the sample reinserted for each measurement. Test samples were preconditioned at room temperature and 50% relative humidity for 24 hours prior to measurement. All sample devices were calibrated in air (empty) and with a polytetrafluoroethylene (PTFE, kept in a 50% humidity environment) control prior to each set of tests. All experiments were performed at room temperature.
[0103] (Table 5) Dielectric constant (dk) and dielectric loss tangent (df) TIFF2025505570000013.tif27149
[0104] The above specification and examples provide a complete description of the structure and use of the exemplary embodiments. Although certain embodiments have been described above with a certain degree of uniqueness or with respect to one or more individual embodiments, those skilled in the art could make numerous modifications to the disclosed embodiments without departing from the scope of the present disclosure. Thus, the various exemplary embodiments of the method and system are not intended to be limited to the particular forms disclosed. Rather, the various exemplary embodiments of the method and system include all modifications and alternatives that fall within the scope of the claims, and embodiments other than the embodiment shown may include some or all of the features of the illustrated embodiment. For example, elements may be omitted or combined in a unitary structure, connections may be substituted, or both. Furthermore, where appropriate, aspects of any of the embodiments described above may be combined with aspects of any other embodiment described to form further embodiments having equivalent or different characteristics and / or functions and addressing the same or different problems. Similarly, it is understood that the benefits and advantages described above may relate to one embodiment or to several embodiments. Therefore, a single implementation described herein should not be construed as limiting, and implementations of the present disclosure may be combined as appropriate without departing from the disclosure of the present disclosure.
[0105] Unless a means-plus-function or step-plus-function limitation is expressly recited in a particular claim using the phrase "means for" or "step for," respectively, the claims are not intended to include, and should not be construed to include, means-plus-function or step-plus-function limitations.
Claims
1. 1. A ceramic-polymer composite powder, comprising: A plurality of composite particles, each of the composite particles being made of a plurality of aluminum oxide (Al 2 O 3 agglomerates of polybutylene terephthalate (PBT) particles physically bonded to the Al particles; 2 O 3 at least some of the particles are exposed on the outer surface of the agglomerate of PBT particles; The powder is 50% to 90% by volume of Al 2 O 3 and 10% to 50% by volume of PBT, the composite particles have a Dv50 of 1 micrometer (μm) to 200 μm; and 90% or more of the PBT is not crosslinked, and the composite particles are in the form of a powder; The ceramic-polymer composite powder.
2. 10. The powder of claim 1, wherein the composite particles comprise 50% to 70% by volume ceramic.
3. 3. The powder of claim 1, having a solvent content of less than 3000 parts per million (ppm).
4. 4. The powder of claim 1, wherein the composite particles have a Dv50 of 10 μm to 30 μm.
5. The Al 2 O 3 5. The powder of claim 1, wherein the particles have a Dv50 of 1 μm to 10 μm.
6. The powder of any one of claims 1 to 5, wherein the PBT particles are clearly identifiable.
7. The Al 2 O 3 7. The powder of any one of claims 1 to 6, comprising less than 5% by weight of free PBT particles that are not directly or indirectly bound to one of the particles.
8. 1-4, optional 2-4 liquidity ff c The powder according to any one of claims 1 to 7, wherein
9. 1. A ceramic-polymer composite material in the form of a pellet, the material comprising: A plurality of solid pellets, each of which contains a plurality of composite particles. Each of the composite particles comprises a plurality of aluminum oxide (Al 2 O 3 agglomerates of polybutylene terephthalate (PBT) particles physically bonded to the Al particles; 2 O 3 at least some of the particles are exposed on the outer surface of the agglomerate of PBT particles; The pellets are 50% to 90% by volume of Al 2 O 3 and 10% to 50% by volume of PBT, Substantially all of the PBT is uncrosslinked; and some of the PBT particles of adjacent composite particles are physically bonded to resist separation of the adjacent composite particles and deformation of each pellet; The ceramic-polymer composite material.
10. 1. A method for forming a ceramic-polymer composite powder, comprising: Polybutylene terephthalate (PBT) particles, organic solvent, and aluminum oxide (Al 2 O 3 ) mixing the particles; at least partially dissolving the PBT particles in the solvent by heating the mixture to a first temperature between the glass transition temperature and the melting point of the PBT while maintaining the mixture at a first pressure at which the solvent remains substantially liquid; stirring the heated mixture for several minutes while maintaining the mixture at or above a first pressure and at or above a first temperature but below the melting point of the PBT; and (a) precipitating at least some of the PBT to form PBT particles; (b) agglomerating at least some of the PBT particles; and (c) removing Al 2 O 3 At least some of the particles are bonded to the PBT particles, thereby forming a plurality of aluminum oxide (Al 2 O 3 cooling the mixture to a second temperature below the glass transition temperature of PBT or to a temperature less than the second temperature to form a plurality of composite particles each comprising an agglomerate of polybutylene terephthalate (PBT) particles physically associated with the Al particles; 2 O 3 at least some of the particles are exposed on the outer surface of the agglomerate of PBT particles; The method comprising:
11. The mixing step comprises: The solvent and the Al 2 O 3 Mixing particles; The solvent and the Al 2 O 3 agitating the mixture with the Al particles; 2 O 3 deflocculating the particles; The PBT is mixed with the solvent and the Al 2 O 3 mixing said stirred mixture with particles.
11. The method of claim 10, comprising:
12. agitating the mixture during the cooling step; filtering the mixture after the cooling step to obtain wet composite particles; washing the composite particles after the filtering step; and drying the composite particles at a temperature above the glass transition temperature of the PBT. The method of any one of claims 10 to 11, further comprising one or more steps selected from the group of steps consisting of:
13. 13. The method of any one of claims 10 to 12, wherein the solvent comprises a solvent selected from the group of solvents consisting of cyclohexanone, orthodichlorobenzene (ODCB), and methoxybenzene.
14. 10. A method comprising the step of subjecting a powder according to any one of claims 1 to 8 or a plurality of pellets according to claim 9 to a first pressure for several minutes while the powder according to any one of claims 1 to 8 is at a first temperature above the melting point of PBT, wherein the powder fills a working portion of a cavity of a mould.
15. 15. The method of claim 14, wherein the first pressure is sufficient to form a molded article with a relative density of greater than 90%, optionally greater than 97%, after the first pressure is applied to the powder for a period of at least 30 minutes.
Citation Information
Patent Citations
Calcium salt-containing composite powder with finely structured particles
JP2019530791A
Particulate compositions comprising metal precursor for additive manufacturing and methods associated therewith
JP2021042372A
Formation material and formation method which are used for forming structure
WO2015199244A1
Resin powder material, laser powder molding method and device
WO2016121013A1
Semi-crystalline polymer-ceramic core-shell particle powders, and processes for making and articles comprising such powders
WO2021059218A2